Does digital footprint act as a digital asset? – Enhancing brand experience through remarketing. (December 2019) - Arya, Vikas; Sethi, Deepa; Paul, Justin
Highlights: Examine utilization of the marketing adaptability of branded mobile apps. Propose a model grounded in the purchaser-brand relationship theory. Enhance the comprehension of the impact of brand on consumer behavior. Abstract: The purpose of this paper is to examine the utilization of the marketing adaptability of branded mobile applications (apps) in order to understand the relationship between consumers and their attachment to branded apps. We develop a model grounded in the purchaser-brand relationship theory of remarketing in order to develop the consumer-brand relationship through mediator brand experience (BE) and moderator digital footprint. A survey was conducted with 421 participants from different regions in India. AMOS 21.0 and SPSS plugin called "Process Analysis System" proposed byHayes (2013) were used to analyze the hypotheses. The results corroborate the proposed research model. It approves brand association with brand connection for those brands that are easily identifiable. The result also confirms that the comprehensive consumption values are the major influencing factors in the adoption of branded apps. The study enhances the comprehension of the impact of brand connotation on consumer behavior in terms of the usage of various branded apps and the practical and non-useful esteem attached to them.